Numerical Simulation on Reappearance of Artillery Barrel Fracture Damage Under the Effect of Abnormal Gas Flow (Dandao Xuebao/Journal of Ballistics, 2023)
Aiming at the occurrence of barrel fracture of a tank gun when firing, the research methods of problem reproduction, reason analysis, calculation analysis and effect verification were adopted. By using the LS-DYNA program fluid-solid coupling algorithm, the high-pressure gas flow generated by the equivalent TNT explosion approximately substituted for the actual gunpowder gas. By using the Lagrangian-Euler coupling algorithm based on explicit integration, the problem of the fluid-solid coupling was solved, and the numerical model of the interaction of the high pressure gas and barrel was set up. The problems of calculation caused by the fluid deformation were solved. The Johnson-Cook plastic and damage evolution model was introduced to describe the dynamic response of barrel material. In the case of presetting initial crack, the dynamic response of the barrel under abnormal internal pressure was numerically analyzed. The results of numerical simulation well described the fracture failure mechanism and reappeared the barrel tearing process. The study offers reference for the safety and fault analysis.